About pathogenesis of depressive state of central nervous system in premature infants - K. V. Dashichev; N. V. Olendar; O. V. Kulibina; E. P. Sitnikova; T. V. Vinogradova (LLC "Diagnostics and Vaccines", 2022)
The study of the neurological status and heart rate variability (HRV) of 65 premature newborns was carried out, of which 25 children had no symptoms of central nervous system (CNS) dysfunction. In 40 children, the neurological status was characterized by symptoms of general CNS depression. Based on the spectral parameters of heart rate variability (HRV), two groups of children with high and low activity of subcortical systems were identified among the latter. In the latter, the syndrome of general CNS depression was characterized by stable symptoms.It is assumed that in this group of premature newborns, this syndrome was caused by insufficient stimulation of the cerebral cortex by subcortical systems due to antenatal inhibition of their activity by exogenous adrenomimetics.